MICROINSTRUCTIONS ARCHITECTURE LEVEL WITH LONG BINARY ARITHMETIC FOR A COMPUTER SYSTEM OF HIGH-PRECISION COMPUTING - Левченко, Андрей; Головко, Алексей (SWorldJournal, 2020)
The paper considers a set of program codes for the following operations, which form the level of architecture of microinstructions with long binary arithmetic for a computer system of high-precision calculations. Partial results of long binary arithmetic